Investigation into the structure and transmission mechanism of a novel multistage face gear transmission based on battery discharge current constant of an electric vehicle. (28th November 2020) - Chen, Xingbin; Hu, Qingchun; Xu, Zhongyang; Liang, Xiaofeng; Li, Jianying; Mai, Qianli; Zhu, Chune
The performance and mileage of an electric vehicle (EV) are usually affected by battery capacity and transmission efficiency. We propose a novel power transmission device, which matches the dynamic performance of a vehicle under limited conditions, such as motor peak power and battery capacity, to ensure working in the constant battery discharge current and high efficiency. Based on the constant current discharge principle of power battery, aiming at the long driving distance of EV, the optimisation design model of structural parameters is established to yield the best transmission ratio and optimal detailed design parameters. We optimised the ADVISOR simulation to verify the speed regulated performance and drive efficiency of the whole transmission system.